Charisma Heuristic as Cognitive Bias: An Informal Category Theoretic Risk Analysis of the Leadership Influence Process - James K. Hazy (Administrative Sciences, 2025)
The notion of charisma has been an important, albeit mysterious, aspect of leadership research for decades. Traditionally, its definition has centered on an individual who, by virtue of possessing certain traits, skills, or behaviors, is considered a natural leader. More recently, however, there has been increasing recognition that charisma is an experience that is actually felt by followers, and therefore perhaps the charisma experience could be better understood by taking a follower’s perspective. This theoretical article addresses this question. It takes the perspective of a follower who reports a charismatic experience and asks the following: What are the benefits and risks to the follower who, by assigning “charisma” to the influence of another, effectively surrenders a measure of individual autonomy by becoming a follower of a leader? This article uses ideas from mathematical category to explore and demystify the notion of charisma in leadership theory and practice. By doing so, it argues that the choice to follow what is considered to be a charismatic other is essentially a decision-making heuristic that carries benefits and risks. A benefit is decreased cognitive load. A risk is the possibility that the leader’s influence will push against a follower’s own interests. Thus, this paper argues that the charisma heuristic should be considered as cognitive bias about which both followers and leaders should be wary. Eight propositions are discussed to inform future research.